U.S. Geographic Differences in Media Source Use During COVID-19 Shelter in Place Orders - Allison R Fortner; Kristin Gibson; Alexa Lamm (Journal of Applied Communications, 2021)
United States news access patterns may have influenced distribution of misinformation in the COVID-19 infodemic, emphasizing the necessity of targeted communication to increase health literacy during a crisis. This study used sense-making theory to explore information-seeking behaviors of U.S. residents during COVID-19 shelter in place orders. This purpose of this study was to identify media outlets used by U.S. residents to access COVID-19 information and determine if access differed according to geographic region. A representative survey of U.S. residents aged 18 or older (N = 1,048) revealed the mainstream media outlets used most were domestic government-based sources. Northeastern and Western residents used all mainstream media outlets more frequently than Southern or Midwestern residents. Chi-square tests determined the regional news-access differences were significant, revealing inconsistencies in information-seeking behaviors. The findings suggest crisis communication plans that affect food and human health must consider regional information-seeking behaviors of U.S. residents to effectively reach target audiences with pertinent information.
Keywords: science communication; information-seeking; crisis communication